2001
DOI: 10.1136/jcp.54.10.787
|View full text |Cite
|
Sign up to set email alerts
|

Wegener's granulomatosis presenting as acute suppurative interstitial nephritis

Abstract: A 78 year old man presented with acute renal failure following a prolonged respiratory illness. A renal biopsy demonstrated severe suppurative interstitial nephritis with normal glomeruli. After nine weeks of antibiotics he remained anuric and a second biopsy demonstrated pauci-immune, necrotising glomerulonephritis. His subsequent clinical course was consistent with a diagnosis of Wegener's granulomatosis and antineutrophil cytoplasmic antibodies (ANCA) were detected. This is the first reported case of Wegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The patient remained dialysis dependent despite treatment with corticosteroids, and cyclophosphamide was commenced thereafter. [2] In our patient, the first renal biopsy, with adequate tissue analyzed to exclude the possibility of focal glomerulonephritis that was not sampled in the biopsy specimen, demonstrated isolated TIN without glomerular lesions. However, there were no detectable common causes of TIN.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The patient remained dialysis dependent despite treatment with corticosteroids, and cyclophosphamide was commenced thereafter. [2] In our patient, the first renal biopsy, with adequate tissue analyzed to exclude the possibility of focal glomerulonephritis that was not sampled in the biopsy specimen, demonstrated isolated TIN without glomerular lesions. However, there were no detectable common causes of TIN.…”
Section: Discussionmentioning
confidence: 57%
“…To our knowledge, only one case of WG with this unique presentation has been described in the literature. [2]…”
Section: Introductionmentioning
confidence: 99%
“…Second, peritubular capillaritis might represent an early event in the course of cryoglobulinemic vasculitis. Transformation from tubulointerstitial nephritis with peritubular capillaritis to crescentic glomerulonephritis in ANCA-associated vasculitis has been reported (25). On average, renal disease in cryoglobulinemic vasculitis is detected at approximately 2.5 years after the onset of disease (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, Nakabayashi et al reported 3 cases (4.5 %) of tubulointerstitial nephritis caused by peritubular capillaritis (PTC) without crescentic glomerulonephritis in a total sample of 66 renal biopsy specimens [4]. In addition, some case reports of ANCA-associated vasculitis described tubulointerstitial nephritis with normal glomeruli in the first renal biopsy and necrotizing crescentic glomerulonephritis in the second renal biopsy [5,6]. These reports suggest that ANCA-associated vasculitis is a condition that involves arteriolitis, crescentic glomerulonephritis, and PTC, and that the characteristics of each are independent.…”
Section: Introductionmentioning
confidence: 94%